Mesangial Localization of Immune Complexes in Experimental Canine Adenovirus Glomerulonephritis - Wright, N. G. (1974)
Each of a group of 14 dogs was infected experimentally by an intravenous dose of canine adenovirus calculated to allow survival until the initial stages of antibody production; the kidneys of infected dogs were examined during the period of 4-14 days after administration of virus. Proliferative glomerulonephritis with localization of IgG, C3 and viral antigen in mesangial regions was demonstrated. With the electron microscope, electron dense deposits were found scattered throughout the mesangium. There was proliferation of mesangial cells, infiltration into the glomerular tuft of polymorphonuclear leucocytes and, in some cases, focal glomerular necrosis with intracapsular and tubular haemorrhage. By means of an indirect immunofluorescence test, anti-viral antibody was detected in kidney eluates; anti-kidney antibody was not present.